"Incidentaloma" of the Liver: Management of a Diagnostic and Therapeutic Dilemma. (8th August 2012) - Ehrl, Denis; Rothaug, Katharina; Herzog, Peter; Hofer, Bernhard; Rau, Horst-Günter
Abstract : The continuous development of highly sensitive clinical imaging increased the detection of focal lesions of the liver. These accidentally detected liver tumors without liver-specific symptoms such as cholestasis have been named "incidentalomas." Diagnostic tools such as sonography, computed tomography, or magnetic resonance imaging are used increasingly in asymptomatic individuals without defined suspected diagnoses in the setting of general prevention or followup after a history of malignancy. But despite continuous improvement of diagnostics, some doubt regarding the benign or malign behavior of a tumor remains. In case an asymptomatic hemangioma or FNH can be preoperatively detected with certainty, the indication for surgery must be very strict. In case of symptomatic liver lesions surgical resection should only be indicated with tumor-specific symptoms. In the remaining cases of benign lesions of the liver, a "watch and wait" strategy is recommended. In case of uncertain diagnosis, especially in patients with positive history of a malignant tumor or the suspected diagnosis of hepatocellular adenoma, surgical resection is indicated. Due to the continuous improvement of surgical techniques, liver resection should be done in the laparoscopic technique. Laparoscopic surgery has lower morbidity and shorter hospitalization than open technique.